The “cancel culture”: contributions from a sociological perspective - Cordeiro, Ana Paula; Martins, Tamires de Assis Lima (Revista Extraprensa, 2024)
Cancel culture as a catch-all term, its abusive utilization to name different situations, its appropriation as a resource to identify any type of collective criticism of the behavior of celebrities on social networks, has led some to defend the inexistence of cancellation as a real social phenomenon, that is, endowed with particularities that distinguish it from mere criticism directed at others. It is a contemporary phenomenon, called "virtual lynching" by its critics, or activism and enlargement of democracy by its defenders, carried out by its executors, apparently, with the aim of problematizing behaviors incompatible, in most cases, with the fundamental values of identity diversity, that is, to expose, deconstruct and demand that racist, sexist, homophobic, transphobic, among others, which constitute dominant prejudices in an unequal society such as Brazil's, be not naturalized. Considering also that a subject is not canceled without the public execration being disseminated to all who want to know about the facts, since the purpose of the cancellation is precisely to reduce to a minimum the symbolic capital, with economic consequences and professionals, so that it serves as an example to deter potential future violators of prevailing ethical and moral norms, the real “cancellations” presuppose the participation of companies or any other economic agent and a relationship of dependence or subordination.Keywords: Cancellation, entertainment, economic dependency, social networks, celebrities.